Gender equality and inequality in rural India : blessed with a son - Vlassoff, Carol; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
Gender Equality in Rural India focuses on son preference and the extent to which economic development has resulted in positive changes in women's empowerment and reproductive health.
Keywords: Science